2007
DOI: 10.1177/0961203307082383
|View full text |Cite
|
Sign up to set email alerts
|

Lupus enteritis: clinical characteristics, risk factor for relapse and association with anti-endothelial cell antibody

Abstract: The study was undertaken to evaluate clinical and laboratory characteristics of patients with lupus enteritis and to investigate its association with anti-endothelial cell antibodies (AECAs). Systemic lupus erythematosus (SLE) patients who were admitted to Kangnam St. Mary's Hospital with complaints of acute abdominal pain from January 1990 to July 2006 were reviewed retrospectively. The clinical features, laboratory data and prognosis of these patients were analyzed. Among the 706 SLE patients admitted during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 30 publications
(56 reference statements)
4
82
0
5
Order By: Relevance
“…Abdominal pain is the most common presenting symptom amongst other non-specific manifestations like ascites, nausea, vomiting, diarrhea and fever and has been shown to be the most common cause of abdominal pain in SLE patients seeking emergency room treatment (6). Typically, the abdominal pain described in lupus enteritis is diffuse in pattern and in some cases accompanied by rebound tenderness and abdominal muscle guarding (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Abdominal pain is the most common presenting symptom amongst other non-specific manifestations like ascites, nausea, vomiting, diarrhea and fever and has been shown to be the most common cause of abdominal pain in SLE patients seeking emergency room treatment (6). Typically, the abdominal pain described in lupus enteritis is diffuse in pattern and in some cases accompanied by rebound tenderness and abdominal muscle guarding (1).…”
Section: Discussionmentioning
confidence: 99%
“…Other than a drop in white blood cell count and complement titres, which may correlate with the occurrence of lupus enteritis, none of the laboratory indices have been found to be useful to establish the diagnosis (5, patient discussed had Low complement levels. Medina et al (7) and Buck et al (8) have reported that gastrointestinal vasculitis or thrombosis in SLE had higher SLEDAI scores than patients with active SLE with non-SLE related acute abdomen, but no such correlation was established by Lee et al (6). However, the presence of autoantibodies against phospholipids and endothelial cells might provide information about the likelihood of recurrence of lupus mesenteric vasculitis (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esta última manifestación se observa en los pacientes que presentan fenómeno de Raynaud (74). Los pacientes con LES pueden tener compromiso de los vasos mesentéricos por vasculitis o trombosis (75).…”
Section: Manifestaciones Gatrointestinalesunclassified